2019
DOI: 10.21608/ejabf.2019.60554
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries status of the bogue Boops boops (Linnaeus, 1758) in Algerian East Coast (Western Mediterranean Sea)

Abstract: Yield per recruit MSY Algeria This study is the first that deals with the stock status of the bogue Boops boops (Linnaeus, 1758) in the Eastern Algerian coast (Western Mediterranean). It aims is to estimate the important parameters needed to evaluate the dynamics of the stock of this species which is economically important resource in Algeria. The FiSAT II software has been used for data analysis. The total length and weight of the fishes sampled ranged from 10.1 to 30.9 cm and from 13.47 to 268.15 g, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Estimates of the total mortality (Z), the natural mortality (M), the fishing mortality (F), and exploitation ratio (E) for the presently reported species were 1.12 y -1 , 0.36 y -1 , 0.76 y -1 and 0.68 which is similar to those for other references: between 1.02 to 2.26 y -1 ; 0.15 to 0.67 y -1 ; 0.66 to 1.59 y -1 and 0.46 to 0.87, respectively. 4,7,20,21,38,39 Our estimate E was 0.68 and higher than 0.50. Gulland 30 suggested that a fish stock is optimally exploited at a level of F which generates E = 0.50, F opt = M. Based on these suggestions, our results mean that the available stock is being heavily exploited.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Estimates of the total mortality (Z), the natural mortality (M), the fishing mortality (F), and exploitation ratio (E) for the presently reported species were 1.12 y -1 , 0.36 y -1 , 0.76 y -1 and 0.68 which is similar to those for other references: between 1.02 to 2.26 y -1 ; 0.15 to 0.67 y -1 ; 0.66 to 1.59 y -1 and 0.46 to 0.87, respectively. 4,7,20,21,38,39 Our estimate E was 0.68 and higher than 0.50. Gulland 30 suggested that a fish stock is optimally exploited at a level of F which generates E = 0.50, F opt = M. Based on these suggestions, our results mean that the available stock is being heavily exploited.…”
Section: Discussionmentioning
confidence: 56%
“…Allen 34 chose to keep the value of the b exponent constant at 3 for isometrical fish growth. The negative allometric growth were recorded from the Gulf of Antalya, 16 in the Morocco waters, 18 in the Egypt waters, 20 and in the Algerian waters, 21 while the positive allometric growth were in the Greece waters, 35 in the Adriatic Sea, 15 and in the Aegean Sea. 13 Variations in fish shape, and growth increase some of the environmental conditions like temperature, season, habitat and food presence.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Mediterranean fisheries rely on this fish. In Algeria, it is ranked 4th in commercial importance after sardine, mackerel and round sardinella, representing 3% of the catch[110]. In all studies except for one (South Sardinia[107]), B. boops shows a high ingestion of MP, especially along the Spanish, French and Italian coasts.…”
mentioning
confidence: 91%
“…has been subject to a number of studies on microplastic ingestion[104] [105] Journal of Water Resource and Protection[106] [107][108]. another fish that is of tremendous commercial importance for the Mediterranean, making for about 20% of the fish landings in the Mediterranean Sea (59% of the landings in Algeria[110]). Numerous studies on the fish[93] [101][108] [111][112] [113] [114] have shown that its MP ingestion is high in most regions of the Mediterranean, where often over 12% of the fish have been found with MP in their gastrointestinal tract with the highest frequency of 96% reported in the Adriatic Sea[115].…”
mentioning
confidence: 99%